Revision surgeries following artificial disc replacement of cervical spine - Jong-Beom Park; Han Chang; Jin S. Yeom; Kyung-Soo Suk; Dong-Ho Lee; Jae Chul Lee (Acta Orthopaedica et Traumatologica Turcica)
Objective: We investigated causes and results of revision surgeries after artificial disc replacement of cervical spine (C-ADR). Methods: Twenty-one patients (mean age: 52.8) who underwent revision surgery after C-ADR and who had a minimum 2-year of follow-up were included into this study. The mean time between the primary and revision surgeries was 21 months. During their primary surgeries, 14 patients underwent single level C-ADR, 2 two-level C-ADR, and 5 two-level hybrid surgery for 16 radiculopathy, 3 myelopathy, and 2 adjacent segment diseases. Causes for revision surgeries were at least one of the followings: 17 poor patient selections, 7 insufficient decompressions, 7 malpositions, 6 subsidences, 3 osteolysis, and 1 postoperative infection. Results: Sixteen patients underwent anterior removal of C-ADR, one-level discectomy and fusion (N = 11), two-level discectomy (N = 3) or one-level corpectomy (N = 2) and fusion. Three patients of keel type C-ADR with heterotopic ossification underwent posterior laminoforaminotomy and fusion. Two patients underwent combined procedures due to infection or severe subsidence and osteolysis. At the 2-year follow-up, neck (7.3 vs 1.6) and arm (7.0 vs 1.3) visual analog scales and Neck Disability Index score (46.7 vs 16.32) were improved (all, p < 0.05). According to Odom's criteria, 86% of the patients were satisfied and 91% achieved solid fusion. No major complications developed except for transient dysphagia in 6 patients (29%). Conclusions: In this small case series, revision surgeries provided successful outcomes in failed C-ADR without major complications. Careful patient selection and meticulous surgical techniques are important to avoid disappointing clinical outcome or even failure of C-ADR. Level of evidence: Level IV, Therapeutic study. Keywords: Revision surgeries, Artificial disc replacement, Cervical spine